1999
DOI: 10.1093/jjco/29.7.336
|View full text |Cite
|
Sign up to set email alerts
|

Serum c-erbB-2 Levels in Monitoring of Operable Breast Cancer Patients

Abstract: Background: Various methods and criteria are used to determine protein overexpression of c-erbB-2 and the clinical utilityof c-erbB-2 is under investigation. We have reported previously that the levelsof cytosol c-erbB-2 in breastcancerwere significantly different between the clinical stages. Methods: The levelsof c-erbB-2protein were determinedin sera from 210 breast cancer patients using a sandwich enzyme immunoassay between November 1996 and March 1998. The cut-off level was set at 5.4 ng/ml for healthy fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In our study, high serum HER2 ECD levels were correlated with stage III (P \ 0.001), large size (C2 cm) (P \ 0.001), positive lymph nodes (P \ 0.001), negative estrogen receptor (P \ 0.001), and progesterone receptor status (P \ 0.001), which was in accordance with the results from most studies (Krainer et al 1997;Isola et al 1994;Yuan et al 2003;Pallud et al 2005;Imoto et al 1999). Furthermore, after validated with other routinely used prognostic factors in multivariate analysis, we found that high serum HER2 ECD levels were significantly associated with DFS and OS, and increased serum HER2 ECD levels had an adverse impact on the prognosis in stage 0-III primary breast cancer patients.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, high serum HER2 ECD levels were correlated with stage III (P \ 0.001), large size (C2 cm) (P \ 0.001), positive lymph nodes (P \ 0.001), negative estrogen receptor (P \ 0.001), and progesterone receptor status (P \ 0.001), which was in accordance with the results from most studies (Krainer et al 1997;Isola et al 1994;Yuan et al 2003;Pallud et al 2005;Imoto et al 1999). Furthermore, after validated with other routinely used prognostic factors in multivariate analysis, we found that high serum HER2 ECD levels were significantly associated with DFS and OS, and increased serum HER2 ECD levels had an adverse impact on the prognosis in stage 0-III primary breast cancer patients.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, higher serum ErbB‐2 was associated with several classical prognostic factors. We previously showed that the expression of cytosol ErbB‐2 was positively related to serum ErbB‐2 in the same breast carcinoma patients 11. Although various methods have been used to determine ErbB‐2 expression, similar results have been reported regarding ErbB‐2 overexpression in tumors and sera from breast carcinoma patients 18, 19, 20.…”
Section: Discussionsupporting
confidence: 54%
“…We previously determined serum ErbB‐2 levels in operable breast carcinoma patients. We found that elevated serum ErbB‐2 was associated with a clinicopathological aggressive phenotype of breast carcinoma and was also related to cytosol ErbB‐2 overexpression 11. In the present study, we evaluated the usefulness of serum ErbB‐2 in preoperative and postoperative breast carcinoma patients.…”
mentioning
confidence: 91%
“…Farzadnia et al 23 did not find correlation between the worst tumor stage and the immunophenotype of HER-2. In the studies by Yuan 39 and Imoto 40 , there was correlation between tumor size and proto-oncogene HER-2. In another survey, carried out by Richi and Junqueira 41 , there was no statistically significant relation between morphological (tumor size, type and histological grading) or molecular factors (ER/PR/ HER-2/KI-67/p53) and the occurrence of metastasis.…”
Section: Discussionmentioning
confidence: 97%